Sosialisasi Kebijakan Perpajakan UMKM yang Baru atas PP No.23 Tahun 2018 Pada Pelaku Usaha Mikro di Kota Depok - Chairil Anwar Pohan; Pebriana Arimbhi; Notika Rahmi; Zulkifli Zulkifli (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2022)
In Indonesia, the development of the micro, small and medium enterprises sector to date has growed up to such an extent that it is almost equal to the number of those working in other formal sectors. In Java, the number of actors in this sector ranges from 37% to 43%, while outside Java it is even more between 40%-55%. Thus, it can no longer be said that the small and medium-sized business sector is only a temporary shelter for workers who have not been able to enter other formal sectors, but its existence is precisely as a growth motor for economic activity (urban) because of the large number of labor absorption. (equal to the number of workers in the formal sector). The existence of Micro, Small and Medium Enterprises (MSMEs) is no longer in doubt because they are proven to be able to survive and become the driving force of the economy. In 2011 MSMEs were able to make a significant contribution to state revenues by contributing 61.9% of gross domestic product (GDP) income through tax payments. In the field of taxation, the government has made special rules to facilitate MSME actors in paying their taxes, namely through PP. 23 of 2018. In this case, we help MSME actors to improve their abilities and understanding in the field of socializing the Tax Regulations. This activity was attended by 37 MSME business actors in Depok City assisted by the Depok Regional Government. After attending the training, participants were given the opportunity to discuss and consult. The results of the training and mentoring show that there is an increase in knowledge about MSME taxation that can be understood by participants and participants become aware of the new tax regulation, namely PP 23/2018 in order to increase their awareness of the importance of paying taxes.